2023
DOI: 10.7759/cureus.40573
|View full text |Cite
|
Sign up to set email alerts
|

Pulp Changes Secondary to Orthodontic Forces: A Review of Literature

Abstract: This review article encompasses the literature pertaining to changes in the dental pulp subsequent to forces exerted secondary to orthodontic treatment. The review was conducted at the College of Dentistry, Qassim University, Saudi Arabia, from October 2022 to February 2023. A literature search was conducted on PubMed, Embase, The Cochrane Library and Google Scholar for articles from 2000 to 2023. Keywords and MeSH terms used were ‘orthodontic forces’, ‘pulp changes’, ‘dental pulpal changes’, and ‘pulp volume’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Orthodontic discomfort and tooth movement are the result of a series of controlled inflammatory reactions involving cells, blood vessels, nerves, and the immune system. 16 These biological processes are connected, with local inflammation being the underlying reason. Pain is induced by the activation of sensory endings by the action of local inflammatory products, such as prostaglandin and bradykinin.…”
Section: The Mechanisms Responsible For Orthodontic Painmentioning
confidence: 99%
“…Orthodontic discomfort and tooth movement are the result of a series of controlled inflammatory reactions involving cells, blood vessels, nerves, and the immune system. 16 These biological processes are connected, with local inflammation being the underlying reason. Pain is induced by the activation of sensory endings by the action of local inflammatory products, such as prostaglandin and bradykinin.…”
Section: The Mechanisms Responsible For Orthodontic Painmentioning
confidence: 99%
“…Orthodontic tooth movement could have multiple consequences on dental pulp. Studies have shown that orthodontic treatment could have a transient inflammatory response on dental pulp [ 1 ], external root resorption [ 2 ], and short-term dental pulp sensitivity [ 3 ], all of which and more should be considered before initiation of orthodontic tooth movement. Multiple factors influence the occurrence of complications during orthodontic tooth movement, such as forces used during movement of teeth [ 4 ].…”
Section: Introductionmentioning
confidence: 99%